1992
DOI: 10.1002/kin.550240807
|View full text |Cite
|
Sign up to set email alerts
|

Disproportionation reactions between alkyl and fluoroalkyl radicals. VII. Difluoromethyl with perfluoro‐n‐propyl and methyl radicals

Abstract: Mixtures of 1,1,3,3-tetrafluoroacetone and perf luorodi-n-propyl ketone have been photolyzed together over the temperature range 50" to 200"C, and the disproportionation/combination ratio for n-C3F7 and CFzH radicals has been determined to be A(n-CsF7, CFZH) = 0.072 ? 0.003. A reevaluation of existing data on CH3 and CFzH radicals leads to a value of A(CH3, CFzH) = 0.35. The large variations in A for the reactions of alkyl and perfluoroalkyl radicals with CFzH radicals are discussed. 0 1992 John Wiley & Sons, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

1992
1992
2004
2004

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…The donor radical contains a CF 3 group at the ␣-carbon and this electronrich substituent may repel an incoming CF 3 acceptor radical, but not a CF 3 CH 2 CHCH 3 radical that has a greater hydrocarbon-radical character. A similar trend has been observed by Pritchard and coworkers [16][17][18][19][20]. For example, when the donor radical was CHF 2 and the acceptor radical was changed from a perfluoro radical to an alkyl radical, k d /k c , for several acceptor radicals, varied as follows: 0.088 (CF 3 ), 0.072 (n-C 3 F 7 ), 0.07 (CHF 2 ), 0.06 (CH 2 F), 0.35 (CH 3 ), 0.37 (C 2 H 5 ), and 0.30 (n-C 3 H 7 ).…”
Section: Figuresupporting
confidence: 88%
See 1 more Smart Citation
“…The donor radical contains a CF 3 group at the ␣-carbon and this electronrich substituent may repel an incoming CF 3 acceptor radical, but not a CF 3 CH 2 CHCH 3 radical that has a greater hydrocarbon-radical character. A similar trend has been observed by Pritchard and coworkers [16][17][18][19][20]. For example, when the donor radical was CHF 2 and the acceptor radical was changed from a perfluoro radical to an alkyl radical, k d /k c , for several acceptor radicals, varied as follows: 0.088 (CF 3 ), 0.072 (n-C 3 F 7 ), 0.07 (CHF 2 ), 0.06 (CH 2 F), 0.35 (CH 3 ), 0.37 (C 2 H 5 ), and 0.30 (n-C 3 H 7 ).…”
Section: Figuresupporting
confidence: 88%
“…When a CF 3 removes an H from the ␣-carbon of the CF 3 CH 2 CHCH 3 radical the k d /k c is within this range, but when the H is from the CH 3 position or when the CF 3 CH 2 CHCH 3 radicals self-disproportionate the values are much higher, 0.24-0.47. Pritchard and coworkers [17] also found that hydrocarbon acceptor radicals have much larger k d /k c ratios than perfluorocarbon radicals. As mentioned previously, Pritchard and coworkers [16][17][18][19][20] found that methyl, ethyl, and n-propyl radicals, accepting an H from CHF 2 , all had k d /k c near 0.3, whereas the k d /k c values were between 0.06 and 0.09 when the acceptor radical was a n-C 3 F 7 or a CF 3 radical.…”
Section: Figurementioning
confidence: 96%
“…The k d / k c ratios also have been measured for many pairs of different radicals . The disproportionation reactions of CF 2 H radicals are interesting cases because the stability of the CF 2 product aids the transfer of H atoms . For cross-disproportionation reactions of CF 3 6 or CH 3 7 radicals with hydrocarbon radicals, the disproportionation channel can be viewed as the abstraction of hydrogen from a weak C−H bond of the hydrocarbon radical.…”
Section: Introductionmentioning
confidence: 99%
“…Recombination and disproportionation are well-established reaction channels for hydrocarbon radicals. , The disproportionation-to-combination ratios, k d / k c , which have been measured for many radicals, are on the order of 0.1 to 0.3 for C 2 −C 4 radicals and independent of temperature. The k d / k c values do depend on the nature of the radicals, as illustrated by the change in k d / k c from 0.14 to 0.30 for self-reactions of ethyl 2 and vinyl radicals .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation